Mathématiques
fuslulu
2

Sinx×cos²x+sin³x-sinx Sinx×cos²x+sin²x-sinx Aide moi svp

+0
(2) Réponses
aylavitale

On sait que: Sin^2 + cos^2=1 Alors: Sinx*cos^2x + sin^3x-sinx Sinx*cos^2 + sinx(sin^2-1) Sinx(cos^2+sin^2-1) Sinx(1-1) = Sinx Sinx*cos^2+sin^2x+sinx Sinx*cos^2+sinx(sinx+1) Sinx(cos^2+sinx+1) Jc plus continuer

Mukasa897

Bonjour, On sait que : cos²(x) + sin²(x) = 1 donc cos²(x) = 1 - sin²(x)     sin(x).cos²(x) + sin^3(x) - sin(x) = sin(x).cos²(x) + sin(x)(sin²(x) - 1)  = sin(x)(1 - sin²(x)) + sin(x)(sin²(x) - 1) = sin(x) - sin^3(c) + sin^3(x) - sin(x)  = 0 Bonne chance

Ajouter une réponse